2015
DOI: 10.1007/s00268-015-2995-7
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Controlled Trial of the Laryngeal Mask Airway Versus the Endotracheal Intubation in the Thyroid Surgery: Evaluation of Postoperative Voice, and Laryngopharyngeal Symptom

Abstract: Use of the LMA in general anesthesia for thyroid surgery has advantages over the ETI in decreasing patients' subjective and objective voice symptoms, reducing the duration of symptoms, and relieving the laryngopharyngeal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…Literature describes the use of the LMA instead of the endotracheal tube particularly in difficulties with intubation. 5 The use of LMAs for thyroidectomy is well described.…”
Section: Discussionmentioning
confidence: 99%
“…Literature describes the use of the LMA instead of the endotracheal tube particularly in difficulties with intubation. 5 The use of LMAs for thyroidectomy is well described.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, most patients with PE are juveniles who have a smaller trachea and are more prone to intubation-related adverse events. The incidence of side effects (laryngeal pain, hoarseness and dysphonia) related to ETT in the early postoperative period has been reported to range from 15% to 50% (19). In such cases, a supraglottic airway device may be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Peirovifar et al (20) reported that postoperative cough, sore throat and difficulty in swallowing were significantly less in the LMA compared to the ETT group. Chun et al (19) also reported that use of the LMA in general anesthesia for thyroid surgery had advantages over the ETT in decreasing patients' subjective and objective voice symptoms, reducing the duration of symptoms, and relieving laryngopharyngeal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…That said, these devices are not devoid of their own risks to the oral cavity and vocal cords. 4 In addition, it has been shown that certain conditions can favour dysphonia or throat pain after short-term endotracheal intubation (Table).…”
Section: To the Editormentioning
confidence: 99%